Osteossínteses de ílio e fêmur em cachorro-do-mato (Cerdocyon thous) - da Silva, Bruna Zafalon; dos Santos, Eduardo Almeida Ruivo; da Costa, Priscila Medina; Goulart, Miúriel de Aquino; Schmitt, Bernardo; Alievi, Marcelo Meller (Acta Scientiae Veterinariae, 2017)
Background: Fractures and dislocations are common orthopedic conditions arising from traumas from anthropic interaction on wild species, such as those caused by road trampling. Among the treatments, osteosynthesis is considered the method of choice in the treatment of fractures, such as ilium body fractures and femoral fractures. Based on this context, with regard to the incidence of auto accidents and few studies describing osteosynthesis techniques for crab-eating fox, the present study aimed to report the osteosynthesis performed on the body of the ileum and femur of a wild specimen of Cerdocyon thous. Case: A female, adult, crab-eating fox (Cerdocyon thous), coming from wild life was referred to hospital care with a history of run over. After specific examinations, it was diagnosed a complete transverse femoral shaft fracture, an oblique ilium body fracture, a pubic and ischial fracture, and pelvic canal narrowing. The treatment instituted was osteosynthesis of the femoral and ilium body fractures through the use of a 2.7 mm locking plate and screws. In the postoperative period, radiographic examination was performed, where bone callus formation was observed in the 5th week and bone remodeling and consolidation in the 11th week. After 140 days of rehabilitation, the animal was able to be released in the wild, with effective return of function of the pelvic limbs. The release was performed by environmental agencies in a national natural reserve, using radio necklace monitoring. Discussion: Osteosynthesis techniques and preoperative and postoperative management proved to be effective for the return of adequate function of the pelvic limbs in Cerdocyon thous. For wild animals, the use of internal orthopedic implants (plate and screws, for example) become the most suitable for osteosynthesis. They decrease the risks of complications resulting from the management, since they require minimal postoperative manipulation. Thus, they maintain the wild behavior of the animal even in captivity. Among the complications observed in the clinical case, we can mention the use of long plate in the osteosynthesis of the ilium body and the narrowing of the pelvic canal as the most relevant. In relation to the pelvic canal narrowing and the reproductive cycle of the species, the crab-eating fox presents monogamous behavior, gestation of 3 to 6 pups per litter and breastfeeding for approximately 3 months. Because litters are relatively large (number of individuals per calving), the pups are relatively small - approximately 120 g at birth -, so it is expected that no complications occur during the gestational period. The treatment of fractures with the use of locking plates was efficient, obtaining bone consolidation at 10 weeks postoperatively, thus corroborating the scientific descriptions for bone consolidation in canids. Finally, the destination for release and monitoring by radiotelemetry was a joint decision between the environmental agencies of the State and the Union. The release decision was based on the maintenance of the wild behavior without evidence of meekness of the specimen, the absence of sanitary restrictions, as well as the population biology and the genetic flow since the release of the animal was carried out near the rescue site. It is concluded that the surgical treatment instituted by the femoral and ilium osteosynthesis was effective for the Cerdocyon thous specimen, culminating in the rehabilitation of the animal and release in the wild.